Enhanced Terahertz Generation From the Lithium Niobate Metasurface - Tu, Yanyun; Sun, Xu; Wu, Haizhong; Zan, Xiaolei; Yang, Yan; Liu, Ning; Wang, Xiaowei; Meng, Congsen; Lyu, Zhihui; Zhu, Zhihong; Liu, Ken; Zhang, Dongwen; et al. (Frontiers in Physics, 2022)
Lithium niobate (LiNbO3) metasurface is an attractive platform for nonlinear frequency conversion due to its excellent nonlinearity, high damage thresholds and strong enhancement of the driving field. Here we demonstrate the nonlinear metasurface for terahertz (THz) generation from LiNbO3 on insulator. The THz electric field from LiNbO3 metasurface of 300 nm thickness is enhanced by more than one order of magnitude compared to unstructured sample. The enhanced terahertz radiation is very selective in the excitation wavelength due to its resonant feature and is highly anisotropic with respect to the excitation polarization. The polarization direction of THz electric field can be controlled by rotating the optical axis of LiNbO3 metasurface. By combining nanofabrication technology of LiNbO3 metasurface and ultrafast nonlinear optics, our work paves the way for the design of new compact terahertz photonic devices that integrate THz emitters into LiNbO3-based chips with multifaceted capabilities.